Monocyte chemoattractant protein-1 as a potential marker for patients with sepsis: a systematic review and meta-analysis - Chen, Zhuo; Li, Chenwei; Yu, Jian (Frontiers in Medicine, 2023)
OBJECTIVE: To investigate the diagnostic value of monocyte chemoattractant protein-1 (MCP-1) as a biomarker for adult patients with sepsis. METHODS: Related studies on the diagnostic value of MCP-1 in adult patients with sepsis were searched in PubMed, Cochrane Library, Embase, CNKI, CBM, Web of Science, Scopus, and Wanfang Data databases (published to February 20, 2023) was performed if studies assessed the diagnostic accuracy of MCP-1 in adult patients with sepsis and provided appropriate information sufficient to construct a 2 × 2 linked table, studies were included. RESULTS: Data from 8 studies with a total of 805 patients were included. The combined sensitivity was 0.84 (95%CI 0.70-0.92), the specificity was 0.82(95%CI 0.67-0.91), the combined positive likelihood ratio was 3.711 (2.119-6.500), the negative likelihood ratio was 0.287 (0.198-0.415), and the area under the working characteristic curve for combined subjects was 0.88. The diagnostic ratio DOR was 16.508 (7.632-35.706). Meta-regression analysis showed that the results were not significant. deeks` funnel plot showed that there was no publication bias. CONCLUSION: According to our Meta-analysis, MCP-1 is a valuable biomarker and may provide evidence for the diagnosis of sepsis in adults.